The dimensions of organizational confidence and its relationship to achieving the strategic position of banks: is an applied research on a sample of private Iraqi banks (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research aims to show the dimensions of organizational trust represented by (administrative policies opportunities for innovation and self innovation and self- realization,availability of information,prevailing organizational values) and its reiationship to achieving the strategic position of banks represented by formation of expectations,buiiding networks,learning operations As the research was applied in each of the banks (middle east)Iraqi investment,Al-Ahly Iraqi, Business Bay, Al- Mansour investment bank),the qusestionnaire was adopted as a tool to collect data and information from the sample number (138)who are in the site (department director, division ,M.division director ,division officer, unit officer)the statistical program(spss) Was used to calcuiate the mean,standard deviation,difference coefficient,correlation coefficient,test,analysis of variance.The research reached anumber of which were:- 1.There is acorrelation between the organizational confidence dimensions and the strategic position.2.There were no differences in the sample response regarding the questionnaire items according to the research banks.